Biologics and Small Molecules for Inflammatory Nail Disorders: A Narrative Review - Carrie A. Forman; Shari R. Lipner (Indian Dermatology Online Journal)
Background: Inflammatory dermatological conditions, including psoriasis, lichen planus, eczema, and alopecia areata, are frequently accompanied by nail findings and can have a significant impact on quality of life. Biologic and small-molecule medications have been approved over the past several decades in treating patients with these inflammatory nail disorders. They may be used in conjunction with longstanding mainstays of treatment (topical and intralesional corticosteroids, topical vitamin D3 analogs). Objectives: Our objectives were to review biologic and small-molecule treatment efficacies for nail psoriasis and alopecia areata-associated nail dystrophy, including Janus kinase inhibitors, apremilast, tumor necrosis factor (TNF) inhibitors, interleukin (IL)-17 inhibitors, and IL-23 inhibitors. Materials and Methods: A comprehensive PubMed literature review of clinical research studies, narrative reviews, systematic reviews, and meta-analyses was performed. Conclusion: Many biologics and small molecules are effective in treating nail psoriasis and alopecia areata, with each requiring precautions for adverse events. Clinical trials for use of biologics and small molecules for nail lichen planus and atopic dermatitis have not been published to date.